Spatio-Temporal Coordination and Conflict of Production-Living-Ecology Land Functions in the Beijing-Tianjin-Hebei Region, China - Zhuxiao Yu; Erqi Xu; Hongqi Zhang; Erping Shang (Land, 2020)
Assessment of multiple land use functions promotes both utilization efficiency of land and regional coordination. Different personal and public products and services are offered by various land use types, meaning their functionality varies. Lack of judgment on temporal trends, turning points, or consideration of multi-source indicators like the ecological and air quality index leads to uncertainties in urban multifunctionality evaluation and functional orientation. In this study, the production-living-ecology land use function index system and evaluation process was improved using an entropy weight, triangle model, and coupling coordination degree. The production-living-ecology land use function (PLELUF) is defined from land use multi-functions. The Beijing-Tianjin-Hebei urban agglomeration was the representative area. The model was applied to quantify land use functions and measure spatio-temporal coordination and conflict from 1990 to 2015. Results found that the production and living functions displayed an overall upward trend and the growth rate of production function is larger, doubling from 1990 to 1995, while living function increases steadily. Ecology function remained steady from 1990 to 2000 but increased afterward. Land use function stage became balanced in ecology-living-production after 2005. No function-balanced cities existed in 1990; nine function-balanced cities were found in 2015. The coupling coordination degree increased from a slight conflict to a high coordination. Land use multi-functionality was high in the north and low in the south in 2015; Beijing had the most significant multifunctionality. This study can aid land use zoning and sustainable land management.